ALIH KODE DAN CAMPUR KODE DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VII SMPN 1 NUNUKAN: Switching Codes and Mixing Codes in Indonesian Language Learning for Students of Grade VII of SMPN 1 Nunukan - Sherry Nabighah, Eva; Usman; Fitri, Sakinah (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to explain the forms of code-switching and code-mixing during the Indonesian language learning process of seventh-grade students at SMPN 1 Nunukan. The method used in this study is descriptive qualitative method applying a sociolinguistic approach. The data used includes students' and teachers' utterances in the learning process that contain elements of code-switching and code-mixing. The subjects of this study include students and teachers. The techniques used to obtain data include field observations and interviews. Meanwhile, the triangulation technique is used to validate the data. Data analysis techniques include reduction, data presentation, and conclusion drawing. The results of the study show findings of code-switching and code-mixing in learning. Metaphorical and situational code-switching was found, as well as code-switching from Indonesian to Malay and from Malay to Indonesian. On the other hand, there were five findings of code-mixing, including the insertion of words that have meaning and can be used for communication. Phrases, which are a combination of two or more words that form a single unit of meaning in a sentence. Clauses, grammatical units. Word repetition, repetition in whole or in part, and idioms/expressions.